The Problems of Expert Witness in Criminal Law - A'yun, Rafiqa Qurrata (Indonesia Law Review, 2014)
The expert testimony is a potential problem in the future due to the impact of the advancement of science and technology. These progressions have an impact on the quality of the crime methods, thus it must be balanced with improving the quality and method of evidence evaluation that requires knowledge and expertise. This paper examines the place of expert witness to be considered as one of the evidence in criminal case investigation and criminal court. I argue that expert qualifications should be determined based on formal education, professional experiences, and the relevance of his expertise with the case. The Criminal Procedure Code (KUHAP) does not restrict the necessary knowledge, so that the expert testimony about criminal law can also become evidence. However, as one of the evidence that can punish or relieve someone, a testimony stated by an expert should be neutral and objective. This objectivity should be based on scientific arguments, not based on the interests of the party who summoned him/her. This study is descriptive analytic using normative juridical literature and empirical data. It also uses the primary data through guided in-depth interview to the judges, public prosecutors, lawyers, and criminal law experts.